Vers une synthèse vocale du français classique à l’aide du logiciel ©KALI - Philippe Caron; Michel Morel (Corela)
This paper deals with the complex issue of the pronunciation of French during the period of King Louis XIV. That question is a keypoint for actors and singers, who need to know how the French language was pronounced in that period. A joint programme between FORELL (University of Poitiers) and CRISCO (University of Caen) research teams was launched in 2004 to collect data from a very large range of sources coming from French speaking countries but also from countries such as Poland or the Low countries or Britain where a good practice of French was a main concern. Not all varieties of French pronunciation are concerned, except for the favoured pronunciation of verses and public occasions. As no direct witness of that period remains any more, scholars have to scrupulously compare those data in order to build up a hypothetic model of its phonetic and prosodic features. A large part of this paper is dedicated to ©KALI computer-aided device which is being implemented by Michel Morel to give an online overview of that pronunciation to any actor or singer needing to assess his/her own practice by 2012.